2020
DOI: 10.3390/nu12020542
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Lactobacillus plantarum Strains on Non-Alcoholic Fatty Liver Disease in High Fat/High Fructose Diet-Fed Rats

Abstract: Emerging evidence suggests that probiotics are beneficial in non-alcoholic fatty liver disease (NAFLD). This study aimed to explore the effects of two Lactobacillus plantarum strains, ATG-K2 and ATG-K6 (isolated from Korean fermented cabbage), in a rat model of high fat/high fructose (HF/HF) diet-induced NAFLD. Rats with NAFLD were randomized into four groups (HF/HF diet control, (HC); HF/HF diet with silymarin, (PC); HF/HF diet with ATG-K2, (K2); and HF/HF diet with ATG-K6, (K6)) with healthy rats on a normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 47 publications
5
34
0
Order By: Relevance
“…In this study, the HFHF diet increased expression of lipogenesis markers FAS and SREBP-1c in the small intestine compared to the normal-diet rats. Oral treatment with L. plantarum ATG-K2 and ATG-K6 reduced expression of these markers in the small intestine, confirming previous findings that L. plantarum ATG-K2 and ATG-K6 affect the liver [ 32 ]. Accumulating evidence has revealed that administration of lactobacilli reduces obesity and decreases the inflammatory response of the small intestine by lactobacilli, though the underlying mechanisms are still not understood.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the HFHF diet increased expression of lipogenesis markers FAS and SREBP-1c in the small intestine compared to the normal-diet rats. Oral treatment with L. plantarum ATG-K2 and ATG-K6 reduced expression of these markers in the small intestine, confirming previous findings that L. plantarum ATG-K2 and ATG-K6 affect the liver [ 32 ]. Accumulating evidence has revealed that administration of lactobacilli reduces obesity and decreases the inflammatory response of the small intestine by lactobacilli, though the underlying mechanisms are still not understood.…”
Section: Discussionsupporting
confidence: 88%
“…Li et al (2014) also showed that L. plantarum NCU116 reduced hepatic fat accumulation and improved liver function as well as decreased endotoxemia in a high-fat-diet-induced NAFLD model. In a rat model of NAFLD induced by high-fat/high-fructose diet, Park et al (2020) showed that Lactobacillus plantarum strains ATG-K2 and ATG-K6 reduced body weight gain, decreased hepatic lipid accumulation, alanine aminotransferase and aspartate transaminase and lower lipogenesis gene expression [ 78 ]. In faecal samples, there were higher proportions of Bacteroidetes and lower Firmicutes.…”
Section: Modulation Of Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…The cholesterol level in the plasma of a high-fat-induced atherosclerosis animal model was decreased by administration of a lactobacillus-rich diet (9). Two strains of Lactobacillus plantarum, ATG-K2 and ATG-K6, can significantly reduce body weight, liver fat accumulation, and related gene expression in non-alcoholic fatty liver disease (NAFLD) rat models generated by a high-fat/high-fructose diet (10). Thus, certain probiotics may be useful as biological agents for preventing and controlling lipid metabolism-related diseases.…”
Section: Introductionmentioning
confidence: 99%